P780 Interchangeability by a biosimilar of infliximab: What do patients think?. (16th January 2018) - Baudrant, M; Roche, A; Allenet, B; Grange, L; Bouillet, L; Mathieu, N; Bonaz, B
Abstract: Background: At the arrival of biosimilars and more particularly those of infliximab, healthcare worker taking care of patients under biotherapy quickly realised the need for harmonised training of professionals to this new concept to avoid the generic pitfalls, poor representations and acceptance. This information made it possible to initiate treatments of biosimilars with the support of patients and physicians. Is the question now of the interchangeability of the original molecule to a biosimilar in patients with chronic disease and treated with biotherapy princeps for several months or even years. Would they agree on a switch? Methods: A survey was conducted in 2016 of 76 IBD patients followed in a day hospital for gastroenterology. The purpose is to gather patient judgment on the interchangeability to a biosimilar of infliximab and identify the barriers and levers for patient acceptance to propose an adapted switch. Twenty-five rheumatology patients and 5 internal medicine patients were also selected to identify transversal notions regardless of the pathology. Semi-structured interviews were conducted based on an interview guide. The reason that choice technique was chosen was to ensure it included a diversity of patient profiles. The interviews were transcribed and a thematic analysis was conducted by two independent professionals. Results: Profile of IBD patients: 57% of women. Average age of 41 years old. 61% had less than three treatments before infliximab. 72% describe side effects with infliximab princeps. 60% are "for" generics. 86.8% have never heard of biosimilars. 56.6% would agree for the switch: mainly agreement in principle and - on the argument of an identical molecule that is to say efficiency and equal tolerance. 27.6% refused the switch: the status quo had confidence in infliximab princeps; they therefore surmised that the switch would be ineffective; their main fear was a loss of efficiency; they had a need for peer's feedback. 15.8% were hesitant and would need to be convinced by the opinion of a specialist; they have fears of side effects and the need to be reassured. The same results were identified for rheumatology and internal medicine patients. Conclusions: These results show the need for communication with patients about the concept of biosimilars. Tools for patients are planned: poster on biotherapy and biosimilars concepts and patient booklets summarising the practical definitions of biotherapy and biosimilars. A discussion with the patient about what he feels under biotherapy princeps seems necessary to reduce the "nocebo effect". The information on biosimilars should be integrated within the proposed support for patients on biotherapy as a component so as not to generate fears over information regarding other treatments.